Do we still need central blocks while we have erector spinae plane block? Case of 2.5 month old infant - Aksu,Can (2019)
Abstract Erector spinae plane block is gaining popularity both for its ease of application and as its comparable effect on postoperative analgesia with central regional techniques like paravertebral block or epidural anesthesia. Its use for many indications has been reported in the literature for pediatric patients. We would like to share our experiences in a 2.5-month infant scheduled for thoracotomy for a giant congenital cyst. Single shot erector spinae plane block was done at T4 level before the start of the surgery for both surgical and postoperative analgesia. No complication was seen during both surgery and follow up period. Erector spinae plane block with the combination of paracetamol was adequate for pain relief.